Body mass index and mortality in relation to age and follow-up of 30 years in large Austrian cohorts. (13th November 2019) - Nagel, G; Peter, R S; Föger, B; Concin, H
Abstract: Background: Obesity and its health consequences will dominate health care systems in many countries during the next decades. Prevention programs have been implemented. However, the optimum body mass index (BMI) in relation to all-cause mortality on population level is still a matter of debate. Material and Method: Data 1/1989-6/2005 of the Vorarlberg Health Monitoring & Prevention Program (VHM&PP, ) and 8/2005-12/2015 for Vorarlberg provided by the Main Association of Austrian Social Security Institutions were analyzed. In both cohorts, information was available on age, sex, measured height and weight as well as the date and cause of death. Generalized additive models were used to model the mortality rate as function of calendar time, age and follow-up. Results: The VHM&PP cohort consisted of 85, 488 men and 99, 873 women and the later of 129, 817 men and 152, 399 women. In the second cohort, men (mean age 48 (SD16.9) vs. 45.3 (SD 15.5) and women (48.3 (SD 17.7) vs. 45.6 (SD 16.6) years) were slightly older than in the VHM&PP cohort. The average BMI was slightly higher in men (26.1 (SD4.0) vs. 25.7 (SD3.8) kg/m2) but not in women (24.6 (SD 4.8) vs. 24.7 (SD 4.9) kg/m2), respectively. In the VHM&PP cohort more ever smokers were found in both men (40.3 vs. 22.4%) and women (24.8 vs. 18.4%) than in the subsequent cohort. BMI optimum increased slightly between 1985 and 2015, from 24.9 (95%-CI: 24.0-25.9) to 26.4 (25.3-27.3) in men and from 22.4 (21.8-23.1) to 23.3 (22.5-24.5) kg/m2 in women. However, age and follow-up had major impact on the increase. In younger age the associations are quite stable, while in men over 50 years and in women over 60 years the BMI optimum decreased with length of follow-up. Conclusions: Overall the BMI optimum increased slightly over time. However, age and follow-up had major impact on the association. These results suggest, that prognosis of obesity related diseases has improved over time. To detangle this further research is necessary. Key messages: In Austria the BMI optimum increased slightly over time. Age and follow-up time had major impact on the association.